Characteristics of Force Transmissibility in PLOVIS-II Cooler Micro-Vibration Isolation System - Yeon-Hyeok Park; Mun-Shin Jo; Hoon-Young Kim; Hyun-Ung Oh (Aerospace)
This study investigates the basic characteristics of force transmissibility for a passive launch and on-orbit vibration isolation system (PLOVIS-II), which was developed to examine the microvibration attenuation of a spaceborne cryogenic cooler. The design, based on a coil spring-type passive vibration isolation system without an additional launch-lock device, demonstrated an effective vibration attenuation performance in both launch and on-orbit vibration isolation. In this study, a test setup and method were developed to measure the force transmissibility of an isolator along each axis using a voice-coil-type non-contact vibration excitation instrument. In addition, the test results included the position sensitivity of PLOVIS-II, considering the worst misalignment of the isolation system, and its performance was compared with that of PLOVIS-I proposed in a previous study.